International Monetary System Dynamics and Global Economic Stability: A Systematic Literature Review - Boedi Satria; Dwi Febri Yolanda (Rangkiang: Journal of Islamic Economics and Business, 2026)
The international monetary system continues to evolve due to increasing global economic integration, changes in the international currency structure, and advances in digital financial technology. These developments significantly influence global economic stability through exchange rates, capital flows, and financial market integration. This study aims to analyze the dynamics of the international monetary system, identify the key factors driving its transformation, and examine their implications for global economic stability. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines using articles retrieved from the Scopus, ScienceDirect, Springer, Emerald Publishing, and Taylor & Francis databases. After the screening process, 29 eligible articles were selected and analyzed using thematic and narrative synthesis. The findings indicate that the international monetary system is primarily shaped by the dominance of the US dollar, monetary policies in advanced economies, financial globalization, international economic crises, and the emergence of Central Bank Digital Currencies (CBDCs). These factors affect exchange rate stability, capital mobility, financial system resilience, and the risk of cross-border crisis transmission. Meanwhile, dedollarization, the growing role of the Chinese yuan, and CBDC adoption present opportunities for a more multipolar and inclusive monetary system despite governance and regulatory challenges. The study contributes by providing a comprehensive synthesis that integrates the drivers, implications, and future prospects of international monetary system transformation into a unified conceptual framework for future research and policymaking.